(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the help of modern technologies for easy learning of foreign languages, using world practice and important theories, to increase the activity of students to study and most importantly, a science reader that can attract the attention of the student. different methods and potential of the teacher are discussed.